UTP Knowledge Based Healthcare Information Services - Sandran, Daarshini Sarath (Universiti Teknologi PETRONAS, 2007)
This report is an extension of the proposal that was submitted for approval as a Final Year Project. It outlines the implementation of UTP Knowledge Based Healthcare Information Services. UTP Knowledge Based Healthcare Information Services will be developed to enhance the current system's functionalities and address issues such as redundancy while providing informative and feedback to system users, who are the staff of UTP Health Clinic, students and lecturer's, to provide a better standard of clinical services. Among the benefits attainable by the UTP Health Clinic with the UTP Knowledge Based Healthcare Information Services are productivity, time savings, improved quality of care and profitability. For implementation, a basis for literature review is determined and steps to conduct this scientific research is determined to derive a hypothesis that builds on the works of others and relating its concepts to implement UTP Knowledge Based Healthcare Information Services. The methodology of the project is discussed where a complete research of the component-based software engineering research is done based on the UTP Knowledge Based Healthcare Information Services case. Finally, the purpose of gathering data together with its conclusions and recommendations are briefly described in this report.